A comparison of meat quality between F1 and F2 pigs crossed by Vietnamese native wild boar and local pigs - Hoang Nghia, Son; Ho Nguyen Quynh, Chi; Le Thanh, Long (Academia Journal of Biology, 2025)
The hybrid wild boar has the advantages of both wild boar and domestic pig, including strong disease resistance, simplicity in captivity, low fat content meat while retaining tenderness and sweetness. This study assesses the meat quality from 8-month-old Vietnamese hybrid wild boars of the F1 and F2 generations. The research subjects are hybrids crossbreeding between the Vietnamese native wild boar with Mong Cai (WM pig) and local pigs in Dak Nong province (WDP pig). Evaluation criteria include carcass performance, pH, and sensory evaluation. The results showed that the hanging carcass ratio and carcass length in F2 hybrid wild boars were slightly higher than that in the F1 generation. Carcass yield in both F1 and F2 generations did not have a significant difference; however, the WM pigs showed a marginally higher carcass yield than the WDP pigs. Changes in pH were not significantly different between groups. WM pigs and WDP pigs exhibited a similarity in backfat thickness. Back skin thickness in group F2 was slightly elevated than F1. Sensory evaluations show that, although there is no difference in taste, F2 generation wild boar meat was gently juicier and more tender than F1 generation. These results indicate that the meat quality of the F2 pigs has not significantly altered from the F1 generation; in fact, several parameters, such as tenderness and juiciness, have slightly improved. This suggests that the F2 generation has maintained the same pork quality as the F1 generation.